2016
DOI: 10.15414/jmbfs.2016.5.special1.44-46
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effect of Amygdalin on the Viability and Steroid Hormone Secretion by Porcine Ovarian Granulosa Cells in Vitro

Abstract: Amygdalin has been one of the most popular “alternative cancer cures” in many European and South American countries. Its anticancer, anti-inflammatory activity and other medicinal benefits have been known for many years. The objective of this in vitro study was to examine the potential impact of amygdalin on the cell viability and production of steroid hormone testosterone by porcine ovarian granulosa cells. Granulosa cells were isolated from porcine ovaries and subsequently cultured without (control) or with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In past decades, amygdalin has been examined extensively. It has possible modulatory impact on cell viability [25] and the steroid production in porcine ovaries in vitro, as Halenár et al [26,27] reported in their study. Michalcová et al [28] published, that natural substances present in apricot seeds may be involved in ovarian folliculogenesis mechanisms of rabbits through inhibition of FSH (follicle-stimulating hormone) levels.…”
Section: Resultsmentioning
confidence: 74%
“…In past decades, amygdalin has been examined extensively. It has possible modulatory impact on cell viability [25] and the steroid production in porcine ovaries in vitro, as Halenár et al [26,27] reported in their study. Michalcová et al [28] published, that natural substances present in apricot seeds may be involved in ovarian folliculogenesis mechanisms of rabbits through inhibition of FSH (follicle-stimulating hormone) levels.…”
Section: Resultsmentioning
confidence: 74%
“…There is a significant amount of evidence for the role of amygdalin on male reproductive functions in animals [21,22,38,43,60], as well as female reproductive system in vivo and in vitro [23,53,[61][62][63][64]. Amygdalin application positively affects ovarian cell viability and stimulates testosterone release by porcine ovarian granulosa cells; therefore, amygdalin can exert a potential effect on cellular growth and the process of ovarian steroidogenesis in vitro [62]. In addition, amygdalin has an evident effect in the treatment of endometriosis, an aggressive disorder associated with infertility, pelvic pain, and intra-abdominal adhesions in women of reproductive age [53].…”
Section: Effects On the Female Reproductionmentioning
confidence: 99%
“…28 days male rabbits antioxidant effect positive [43] 5 mg/kg/week i.p. 42 days female rats protective effect against endometriosis positive [53] In vitro studies 0.5, 1, 2.5 and 5 mg/mL 5 h rabbit spermatozoa stimulatory effect positive [60] 1, 10, 100, 1000 and 10,000 µg/mL 24 h porcine ovarian cells stimulatory effect positive [61][62][63][64]…”
Section: Effects On the Female Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, natural biomolecules and their impact on reproductive functions have attracted a huge scientific attention (Kolesarova et al, 2011;Halenar et al, 2016;Packova et al, 2016;Roychoudhury et al, 2018). Naturally-occurring phytocompounds from dietary fruits and vegetables have received public interest for the prevention and treatment of various diseases (Modaeinama et al, 2015;Sharma et al, 2017).…”
Section: Figurementioning
confidence: 99%